Covid-19: statutory means of scrutinizing workers' deaths and disease. (21st September 2020) - Agius, R M
Abstract: Background: By law, covid-19 disease and deaths in workers may lead to coroners' inquests and/or Health and Safety Executive (HSE) investigations. Aims: This study assesses the adequacy of these statutory means to yield recommendations for prevention of acquiring covid-19 infection from work. Methods: Covid-19 guidance from the chief coroner and the HSE was appraised, including using Office for National Statistics (ONS) data. Practitioners were asked to estimate the likelihood that covid-19 disease may have arisen from 'near-miss' scenarios. Data from the judiciary and the HSE were analysed. Results: The coroners' guidance allowed a wider range of reports of death than did the HSE and conformed better with ONS data on covid-19 mortality by occupation. In the practitioner survey, 62 respondents considered a higher likelihood that reported covid-19 cases would have arisen from the scenario deemed unreportable as a 'dangerous occurrence' by HSE than the reportable scenario ( P < 0.001). On average there was only one coroner's report to prevent future death from occupational disease every year in England and Wales. The HSE dealt with a yearly average of 1611 reports of work-related disease including 104 on biological agents, but has received about 9000 covid-19 reports. Conclusions: Current HSE guidance for reporting work-related covid-19 may miss many thousands of cases and needs further iteration. Coroners have very limited experience of inquiry into occupational disease caused by biological agents compared with the HSE. Concerns regarding national policy such as on protective equipment warrant a full public inquiry.